Mechanisms of dark personality traits in lesbian adult attachment: a chain-mediated model - Ye Liu; Shujiao Li; Shaoyang Ma; Shaoyang Ma (Frontiers in Psychology)
IntroductionRecent years have witnessed a growing focus on the mental health of sexual minorities, however research on the adult attachment styles of lesbians remains limited. This study examined the impact of dark personality traits on adult attachment, as well as the mediating roles of internalised homophobia and self-esteem among lesbian women.MethodsA total of 1136 lesbians (Mage = 21.57, SDage = 3.716) were surveyed using the Dirty Dozen, the Experiences in Close Relationships Inventory, the Internalised Homophobia Scale, and the Rosenberg Self-Esteem Scale. With dark personality traits as the independent variable, internalised homophobia and self-esteem as the mediating variables, and the two dimensions of adult attachment as the dependent variables, the relationship among these the variables was tested using the PROCESS plug-in for SPSS version 27.0.ResultsThe results indicated that dark personality traits are strongly correlated with internalised homophobia and are a significant factor influencing it (β = 0.052, p < 0.001). Internalised homophobia, in turn, significantly negatively impacted self-esteem (β = −0.039, p < 0.001). Furthermore, self-esteem significantly negatively influenced both attachment avoidance (β = −1.033, p < 0.001) and attachment anxiety (β = −1.246, p < 0.001). These findings support the chain mediation hypothesis, revealing three distinct pathways: (1) dark personality traits → internalised homophobia → attachment avoidance, attachment anxiety, (2) dark personality traits → self-esteem → attachment avoidance, attachment anxiety, and (3) dark personality traits → internalised homophobia → self-esteem → attachment avoidance, attachment anxiety.DiscussionThese results highlight the significant impact of dark personality traits on attachment patterns among lesbians, offering valuable insights for counselling and clinical practice tailored to lesbians.